FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN APD PADA PEKERJA PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) - Anita Dian Permata Sari; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat, 2019)
Personal protective equipment (PPE) was a tool used by workers to protect themselves from potential hazards and accidents that are likely to occur in the workplace. They are required to use PPE in accordance with the Governor Regulation of the Special Province of Jakarta Capital City Number 6 of 2016 to minimize workplace accidents and occupational diseases. This study aimed to analyze the relationship between age, working period, education, knowledge, attitude, supervision, co-workers and available of PPE with the complience to use PPE in workers in PPSU workers in . The research used analitic observation method with cross-sectional approach. The population of this study was 98 people and 49 sample were taken. The sampling technique using simple random sampling. Instrument research used questionnaire and checklist. The results of this study indicate that 79.6% of respondents do not comply using PPE. Based on the chi-square test, the variables related to compliance with PPE use were education level (p = 0.030), knowledge (p = 0.021), attitude (p = 0.003), supervision (p = 0.037) and co-workers (p = 0.037) . While the variables that are not related to compliance with the use of PPE are age (p = 1,000), working period (p = 0.459) and the availability of PPE (p = 0.311). The researcher gave advice to the office to make an SOP on the use of PPE and to disseminate it to PPSU workers so that they understood about the function of PPE.